2005
DOI: 10.1016/j.soildyn.2004.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Seismic wave amplification: Basin geometry vs soil layering

Abstract: The main purpose of the paper is to analyze seismic site effects in alluvial basins and to discuss the influence of the knowledge of the local geology on site amplification simulations. Wave amplification is due to a combined effect of impedance ratio between soil layers and surface wave propagation due to the limited extent of the basin. In this paper, we investigate the influence of the complexity of the soil layering (simplified or detailed layering) on site effects in both time and frequency domain. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(77 citation statements)
references
References 22 publications
2
75
0
Order By: Relevance
“…The orientation of the ridges relative to such shaking pattern may result in different resonance behaviour of the ridges (as known to occur for sedimentary basins, e.g. Rial et al, 1992;Semblat et al, 2005) and shown by Bouchon (1973). Segments orientated at one azimuth may experience amplification of shaking and in contrast, the other ridge-system at different azimuths may experience relative damping or less forcing.…”
Section: (Iv) Shaking Pattern Relative To Azimuthmentioning
confidence: 98%
“…The orientation of the ridges relative to such shaking pattern may result in different resonance behaviour of the ridges (as known to occur for sedimentary basins, e.g. Rial et al, 1992;Semblat et al, 2005) and shown by Bouchon (1973). Segments orientated at one azimuth may experience amplification of shaking and in contrast, the other ridge-system at different azimuths may experience relative damping or less forcing.…”
Section: (Iv) Shaking Pattern Relative To Azimuthmentioning
confidence: 98%
“…For example, Semblat et al (2005) study the influence of the complexity of the media geometry when computing the 2-D Volvi basin response in Greece. Guidotti et al (2011) assess the role of basin geometry and kinematic seismic source in 3-D ground motion simulation of the 2011 February 22 M w 6.2 Christchurch earthquake.…”
mentioning
confidence: 99%
“…In the surface layer, surface waves are formed. Many authors have studied the phenomenon of propagation and amplification of seismic waves in soils (Driad-Lebeau et al 2009;Semblat et al 2000Semblat et al , 2005. Surface waves have the greatest impact on surface structures, particularly their horizontal components.…”
Section: Assumed Kinematic Loads and Dynamic Analysismentioning
confidence: 99%